Synthesis, structural studies, and cytotoxic evaluation of novel ursolic acid hybrids with capabilities to arrest breast cancer cells in mitosis. Issue 3 (4th March 2017) - Pattnaik, Banita; Lakshmi, Jerripothula K; Kavitha, Rachineni; Jagadeesh, Bharatam; Bhattacharjee, Debanjan; Jain, Nishant; Mallavadhani, Uppuluri V.
Abstract: Some novel chemically modified frameworks of ursolic acid have been designed and synthesized. The key step was the cycloaddition of azidopropyl-3β-hydroxy-urs-12-en-28-oate with the appropriate C28 propargyl esters of ursolic, corosolic, asiatic, oleanolic, and betulinic acid under Click reaction conditions, and the products were obtained in 74–84% yields. In view of their intriguing structural diversity, they have been subjected to detailed 1D and 2D NMR studies and their structures are thoroughly assigned. The synthesized compounds were screened for their anticancer potential against two human breast cancer cell lines (MCF-7 & MDA-MB-231) using sulforhodamine B cell proliferation assay. The GI50 data revealed that the synthesized compounds exhibit highly potent activities against the two tested cell lines. Interestingly, the synthesized compounds showed selectivity and higher activity against MDA-MB-231 cell line than MCF-7. Among the tested compounds, compound17 is the most potent one with GI50 value of 1.4 ± 0.1 μM and showed 2.9 times more activity than the standard doxorubicin against MDA-MB-231. In addition, 17 arrests cells in mitotic phase of cell cycle, resulting in a change in cell phenotype. In view of the selective and highly promising activity against breast cancer cell lines, these compounds can serve as promising leads for further development.